Development of a quality control manual for skinless pork "longanisa" - Alameda, Mariza Yvette Baguinon (1994)
This study aims to develop a quality control manual for skinless pork "longanisa". The first phase was devoted to the development of a product profile for skinless pork "longanisa" using the formulation and process of the Bureau of Animal Industry (B.A.I.). This was compared to three other similar products already sold in the market. The B.A.I. formulation and process for skinless pork "longanisa" was found to be the most acceptable among the four brands. For this reason, no product improvement is need and so the process is now ready for standardization. Phase II involved three laboratory scale productions using one kilogram of meat per batch. The major raw material, meat, and the products from this phase were subjected to physico-chemical tests, proximate analysis and microbiological examinations. Sensory evaluation of the finished product indicated moderate acceptability for the skinless pork "longanisa". Three batches of pilot scale production was done using the formulation and process developed in Phase II. The major raw material and products in this phase were also subjected to the same tests as in Phase II. Results of the sensory evaluation indicated moderate acceptability.